Pengembangan Model Pembelajaran PBL Berbantuan Media Canva Pada Mata Kuliah Menulis Bahan Ajar Mahasiswa Pendidikan Bahasa dan Sastra Indonesia IKIP Siliwangi - Nugraha, Via; Wuryani, Woro; Sapdiani, Ratih (P2M STKIP Siliwangi, 2024)
Writing teaching materials is a course given to prospective teaching students. In general, teaching materialscreated by teachers are still conventional. One of the supports for successful learning is media. The researchwas carried out with the aim of: 1) student teacher educators can follow technological developments in writingteaching materials using the Problem Based Learning (PBL) method assisted by Canva media and 2) measurestatistically the level of success of students in writing teaching materials using PBL. The research method usedwas quantitative with a sample of Indonesian Language and Literature Education students at IKIP Siiwangiclass of 2020 class A1 and A2. This research uses a nonequivalent control group design experimental methodby providing treatment to two different classes. The learning results show that both classes have experiencedimprovements in writing teaching materials. However, based on the N-gain test, the results of creativity andoptimization of students' abilities in the experimental class obtained an N-gain of 0.2884, while the controlclass was 0.0572. Based on this test, it can be concluded that the experimental class's ability to write teachingmaterials was much better than the control class. This improvement includes aspects such as writing structure,use of language, creativity & innovation, understanding of material and reader involvement.